Descending facilitatory control of mechanically evoked responses is enhanced in deep dorsal horn neurones following peripheral nerve injury - Suzuki, Rie; Rahman, Wahida; Hunt, Stephen P; Dickenson, Anthony H (Brain research, 2004)
Pain resulting from peripheral nerve injury, characterised by ongoing pain, hyperalgesia and allodynia arises from peripheral and central processes. Here, we studied the potential role of central facilitations in nerve injury by investigating the effect of blocking the excitatory 5HT3 receptor with ondansetron. 5HT3 receptors play a pronociceptive role in the spinal cord and ondansetron has previously been shown to produce antinociception in behavioural studies. We investigated the effects of spinally administered ondansetron (10, 50 and 100 μg) on the responses of deep dorsal horn neurones, evoked by peripheral electrical stimuli and a range of natural (mechanical punctate and heat) stimuli, 2 weeks after nerve injury induced through tight ligation of L5/6 spinal nerves (SNL). Comparisons were made between SNL rats and a sham-operated group. Ondansetron produced little effect on the electrically evoked responses (Aβ-, Aδ- and C-fibre-evoked responses, postdischarge); however, responses to mechanical punctate stimuli (von Frey filaments 1–75 g) were markedly reduced in both SNL and control groups. Furthermore, the drug effect was significantly enhanced after SNL (p<0.05). In particular, the lowest dose (10 μg) now became effective after SNL. Ondansetron produced less marked effects on thermal responses. Our results demonstrate that neuropathic pain states are associated with an enhanced descending facilitatory control of mechanical responses of spinal neurones, mediated through the activation of spinal 5HT3 receptors. These excitatory influences are likely to contribute to the development and maintenance of central sensitisation in the spinal cord, and furthermore, to the behavioural manifestation of tactile allodynia.